Strain-release glycosylation using donor-acceptor cyclopropanes: development and applications in carbohydrate synthesis - Ding, Han (Nanyang Technological University, 2024)
Carbohydrates are essential biological molecules that can mediate diversified biological processes including cell-cell signalling, adhesion, and growth. Vital utilities in drug and vaccine development of these essential compounds translate to keen demand for their acquisitions. However, the relatively low-concentration natural occurrence and microheterogeneity prohibit the direct isolation of significant amounts of sugar molecules from biological resources. Therefore chemical glycosylation becomes one of the most reliable approaches for large-scale preparations of carbohydrates with well-defined structures.